Local knowledge of traditional medicinal plants use and education system on their young of Ammatoa Kajang tribe in South Sulawesi, Indonesia - Siti Zubaidah; Suhartini Azis; SUSRIYATI MAHANAL; JATI BATORO; SUTIMAN B. SUMITRO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Azis S, Zubaidah S, Mahanal S, Batoro J, Sumitro SB. 2020. Local knowledge of traditional medicinal plant use and education system on their young Ammatoa Kajang tribe in South Sulawesi, Indonesia. Biodiversitas 21: 3989-4002. Kajang tribal community in Indonesia has been using plants as traditional medicine for long periods of time; however, this traditional knowledge has not been appropriately documented. Therefore, to prevent the knowledge from being degraded or vanished, it needs to be documented. This study aimed to (i) document the local knowledge of Ammatoa Kajang tribe on the use of traditional medicinal plants, (ii) describe the education system of their young generation, and (iii) conduct Informant Consensus Factor (ICF) and Use Value (UV) analyses. The research data were obtained from 114 informants through semi-structured interviews. This research uses descriptive analysis, quantitative ICF, and UV. A total of 104 plant species from 50 families were identified. Parts of plants that were frequently used by the tribal community were leaves (48.56%). Before using the medicinal plants, the people customarily boiled (33.09%) the plants. The youth received education through informal education that became the highest level of education delivered orally by the family (51.75%). The highest ICF was found in the Digestive System Diseases category, and the highest UV was observed in Piper betle.